Slow tourism at lake Tisza: experience and development prospects - Vargáné Gálicz Ivett; Варга Галіц Іветт; Fodor Gyula; Фодор Дюло; Berghauer Sándor; Бергхауер Олександр; Tóth Attila; Товт Атілла; Dávid Lóránt Dénes; Давід Лорант Денеш (Видавничий дім «Гельветика», 2024)
Abstract. Slow tourism is growing quickly in Hungary. It offers the opportunity to immerse oneself in a new way of life and experience an old-new way of life. It represents a sustainable form of tourism focusing on slowing down the pace of life and exploring local culture, nature, gastronomy and communities. The experiential approach to tourism aims to recharge the body, mind and spirit while minimizing the ecological footprint.The study explores slow tourism at Lake Tisza, focusing on the Sarud Experience Village. It examines how the village uses local resources and resident involvement to create a distinctive slow tourism experience. The primary objective is to analyze the impact of the Sarud Experience Village on visitor satisfaction and the quality of life of the local community. The research aims to show how slow tourism principles enhance visitor experiences while meeting their needs. It combines quantitative and qualitative methods. Primary data were collected through a questionnaire survey among regular visitors to the Sarud Experience Village. Secondary data included a literature review on slow tourism and rural development, along with field visits and observations. The Sarud Experience Village successfully applies slow tourism principles by focusing on traditional lifestyles and a close connection to nature. Survey results indicate high visitor satisfaction with services, the environment, and staff professionalism, though feedback on pricing was mixed. The success of the Sarud Experience Village model suggests potential applications in other rural areas aiming to boost tourism while preserving local culture and environment. The project demonstrates that slow tourism can be a sustainable and impactful approach to rural development, offering economic benefits and improving residents' quality of life. The Sarud Experience Village exemplifies successful slow tourism by balancing visitor satisfaction with community development. The research highlights the importance of integrating local resources and resident involvement in creating authentic and sustainable tourism experiences.

Резюме. Повільний туризм швидко розвивається в Угорщині і пропонує можливість зануритися у новий життє-вий стиль та відчути старий-новий спосіб життя. Він являє собою сталу форму туризму, яка зосереджена на уповільненні темпу життя та дослідженні місцевої культури, природи, гастрономії і спільнот. Експе-риментальний підхід до туризму має на меті зарядити тіло, розум і дух, мінімізуючи його екологічний слід.Дана робота досліджує повільний туризм на озері Тиса у фокусі із селом розваг Шаруд. Проаналізовано, як село використовує місцеві ресурси і власних жителів для створення своєрідного досвіду повільного туризму. Основна мета дослідження – оцінити вплив діяльності села розваг Шаруд на рівень задоволеності відвідува-чів, а також на якість життя представників місцевої спільноти. Робота має на меті показати, як принци-пи повільного туризму посилюють приємні враження відвідувачів, задовольняючи їхні потреби. Вона комбі-нує кількісні та якісні методи дослідження. Первинні дані були зібрані за допомогою анкетного опитування серед регулярних гостей села розваг Шаруд. База вторинних даних включала в себе огляд фахової літератури стосовно повільного туризму та розвитку сільських місцевостей поряд із польовою практикою та спосте-реженнями на місці. Село розваг Шаруд удало застосовує принципи повільного туризму, акцентуючи увагу на традиційному стилі життя і тісних зв’язках із природою. Результати анкетування доводять високий рівень задоволеності відвідувачів послугами, середовищем, а також професіоналізмом персоналу, хоча думки стосовно рівня та діапазону цін суттєво відрізняються. Успіх моделі села розваг Шаруд спонукає на її потен-ційне розширення у напрямі інших сільських районів із метою підвищення туристського обороту, зберігаючи цим самим місцеву культуру та середовище. Проєкт доводить, що повільний туризм може стати стійким і значущим підходом до сільського розвитку, обіцяючи економічні переваги та покращуючи умови життя міс-цевих мешканців. Село розваг Шаруд є прикладом удало створеного повільного туризму, балансуючи задоволе-ність відвідувачів із розвитком суспільства. Дослідження підкреслює важливість інтеграції місцевих ресурсів і участі локальних жителів у формуванні автентичного та стійкого туристичного продукту.
Повільний туризм на озері Тиса: досвід та перспективи розвитку
Редакція: https://journals.kmf.uzhgorod.ua/index.php/geograph/editorial
Зміст: https://journals.kmf.uzhgorod.ua/index.php/geograph/issue/view/3
Keywords: slow tourism; rural development; Hungary; Lake Tisza; Sarud Experience Village